Challenges of the HOW Journal in Spreading Teachers' Works in Times of Ranking Pressures - Melba L. Cárdenas (Asociación Colombiana de Profesores de Ingles, 2016)
Colombian universities and some professional organisations have faced the challenge of gaining visibility, mainly via accredited publications whose reputation depends upon their inclusion in prestigious rankings. This article contains a documentary analysis of the evolution of the HOW journal, the authors' profiles, and their preferred themes and concerns-as evidenced in the articles published to date and in records of the editorial processes kept over the past ten years. From that analysis we derive a series of challenges dealing with editorial policies and processes which are closely related to current trends in the evaluation systems that govern the rankings of academic journals.